Mini droplet, mega droplet and stripe formation in a dipolar condensate - Young-S., Luis E.; Adhikari, S. K. [UNESP] (Elsevier, 2023)
We demonstrate mini droplet, mega droplet and stripe formation in a dipolar 164Dy condensate, using an improved mean-field model including a Lee–Huang–Yang-type interaction, employing a quasi-two-dimensional (quasi-2D) trap in a way distinct from that in the pioneering experiment, M. A. Norcia et. al., Nature 596, 357 (2021), where the polarization z direction was taken to be perpendicular to the quasi-2D x–y plane. In the present study we take the polarization z direction in the quasi-2D x−z plane. Employing the same trapping frequencies as in the experiment, and interchanging the frequencies along the y and z directions, we find the formation of mini droplets for number of atoms N as small as N=1000. With the increase of number of atoms, a spatially-periodic supersolid-like one-dimensional array of mega droplets containing 50000 to 200000 atoms is formed along the x direction in the x–y plane. These mega droplets are elongated along the polarization z direction, consequently, the spatially periodic arrangement of droplets appears as a stripe pattern in the x−z plane. To establish the supersolidity of the droplets we demonstrate continued dipole-mode and scissors-mode oscillations of the droplet-lattice pattern. The main findings of the present study can be tested experimentally with the present know-how.
Keywords: Bose–Einstein condensate; Mega droplet; Mini droplet; Strongly dipolar condensate; Supersolid